2014
DOI: 10.1002/sia.5434
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization of lignocellulosic biomass submitted to pyrolysis

Abstract: The aim of this work was to determine changes in the surface composition and structure of different biomass samples submitted to high temperature treatment. Cellulose and lignocellulosic biomass were pyrolysed in a stirred batch reactor under atmospheric pressure at 700 °C for 4 h. The reaction was executed without and in the presence of Ni/ZrO2 catalyst. Different biomass samples and the remaining residues after the pyrolysis were investigated by time‐of‐flight SIMS, infrared spectroscopy, and SEM. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Moreover, the literature data demonstrated that the activity of Ni based systems dropped considerably in the presence of real biomass samples due to more complex composition of the used feedstock (i.e. presence of lignin or different organic and inorganic contaminants) [17]. Therefore, we also focused in this work on the investigation of the influence of various types of biomass on the performance of Ni/ ZrO 2 catalyst modified by CaO in the production of hydrogen rich gas.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the literature data demonstrated that the activity of Ni based systems dropped considerably in the presence of real biomass samples due to more complex composition of the used feedstock (i.e. presence of lignin or different organic and inorganic contaminants) [17]. Therefore, we also focused in this work on the investigation of the influence of various types of biomass on the performance of Ni/ ZrO 2 catalyst modified by CaO in the production of hydrogen rich gas.…”
Section: Introductionmentioning
confidence: 99%
“…ToF-SIMS is used for identification of biomass surface composition through the bombardment of the sample by short pulses of primary ions interacting with the investigated surface [52,53]. ToF-SIMS has been used to investigate a wide array of solid materials, such as polymers, biological samples, metals, catalysts and archeological objects [52,[54][55][56][57][58]. During ToF-SIMS analysis, chemical bonds are broken with secondary ions initially emitted from the sample and directed to the mass analyzer [59].…”
Section: Introductionmentioning
confidence: 99%